Handbook of sea-level research - Shennan, Ian; Long, Antony; Horton, B. P. (Benjamin P.) (Wiley-Blackwell, 2015)
"This book will cover all aspects of modern sea-level studies, with a focus on the most robust scientific approaches and techniques"--